Competency Level of Service Crew in Rinconada, Philippines - Bulalacao, Rosalie; Repatacodo, Jairo N. (Journal of Social and Community Development, 2025)
The level of competencies of the service crew in fast food restaurants plays a crucial role in delivering quality service, ensuring customer satisfaction, and maintaining operational efficiency. The study aimed to determine the level of competencies of the service crew in Rinconada. Specifically, it focuses on competencies desired by the fast-food industry along communication, team environment, professionalism, and effectivaThe level of competencies of the service crew in fast food restaurants plays a crucial role in delivering quality service, ensuring customer satisfaction, and maintaining operational efficiency. The study aimed to determine the level of competencies of the service crew in Rinconada. Specifically, it focuses on competencies desired by the fast-food industry along communication, team environment, professionalism, and effective customer relations and the level of competencies along with basic competencies, common competencies, and core competencies in cookery and food and beverage service. A descriptive research method was used. The study's respondents are 147 service crew in Rinconada who have been in the service for at least 2 years and are of legal age. A self-made questionnaire was utilized. Findings. Fast food restaurants need a service crew that is highly competent in communication, team environment, and professionalism and in providing effective customer service. The service crew in fast food restaurants in Rinconada is very competent in common competencies and core competencies in cookery and food and beverage service while competent in the common competencies. Recommendations. Fast food restaurants implement regular skills training programs, provide mentorship opportunities, and conduct performance assessments to enhance the competencies of service crew members while aligning with the desired standards of the establishment and being globally competitive. e customer relations and the level of competencies along with basic competencies, common competencies, and core competencies in cookery and food and beverage service. A descriptive research method was used. The study's respondents are 147 service crew in Rinconada who have been in the service for at least 2 years and are of legal age. A self-made questionnaire was utilized. Findings. Fast food restaurants need a service crew that is highly competent in communication, team environment, and professionalism and in providing effective customer service. The service crew in fast food restaurants in Rinconada is very competent in common competencies and core competencies in cookery and food and beverage service while competent in the common competencies. Recommendations. Fast food restaurants implement regular skills training programs, provide mentorship opportunities, and conduct performance assessments to enhance the competencies of service crew members while aligning with the desired standards of the establishment and being globally competitive.